Assessing the effect of a canine surgical-neutering educational programme on the knowledge and confidence of Indian veterinary participants - Rayner, Emma L.; Airikkala-Otter, Ilona; Mellanby, Richard J.; Gibson, Andrew D.; Susheelan, Aswin; Gamble, Luke; Mazeri, Stella (Frontiers in Veterinary Science, 2023)
India has a large, free-roaming dog population, encompassing both owned and stray dogs. Canine surgical neutering is often a central component of dog population management and rabies control initiatives. The provision of practical, surgical training opportunities remains a major challenge for veterinary educational establishments worldwide to ensure competency in this routine procedure. A 12-day educational programme, focusing on surgical neutering skills, was developed to address this need. A questionnaire comprising 26 questions covering surgical and clinical topics, and a self-assessment of confidence in undertaking five common surgical procedures, was completed immediately before and after finishing the programme. A total of 296 participants attended, with 228 achieving the inclusion criteria for the study. Total knowledge scores increased significantly after the training programme (mean score pre- 18.94, 95% CI 18.13-19.74; post- 28.11, 95% CI 27.44-28.77, P<0.05) with improvements seen in all categories (surgical principles, anaesthesia, antibiotic use and wound management). After accounting for other participants’ characteristics, scores increased, on average, by 9 points after training. Characteristics associated with significantly higher scores overall were being female and within the youngest age group (21-24 years old). Amongst those with post-graduate qualifications, overall scores increased with age. Furthermore, there was an increase in self-rated confidence by participants in undertaking all five procedures. This study demonstrates that a targeted training programme can improve veterinarians’ knowledge and confidence in canine surgical neutering and may provide an effective way to develop surgical expertise amongst veterinarians engaged in dog population management initiatives.